2023
DOI: 10.7150/thno.83543
|View full text |Cite
|
Sign up to set email alerts
|

MOF-derived bimetallic nanozyme to catalyze ROS scavenging for protection of myocardial injury

Abstract: Rationale: Myocardial injury triggers intense oxidative stress, inflammatory response, and cytokine release, which are essential for myocardial repair and remodeling. Excess reactive oxygen species (ROS) scavenging and inflammation elimination have long been considered to reverse myocardial injuries. However, the efficacy of traditional treatments (antioxidant, anti-inflammatory drugs and natural enzymes) is still poor due to their intrinsic defects such as unfavorable pharmacokinetics and bioavailability, low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…ROS, whether exogenously or endogenously overproduced, can lead to an imbalance in redox homeostasis [ 42 ]. Although elevated levels of virus-induced ROS trigger innate antiviral immunity, a recent study reported that ROS production is beneficial for viral replication [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…ROS, whether exogenously or endogenously overproduced, can lead to an imbalance in redox homeostasis [ 42 ]. Although elevated levels of virus-induced ROS trigger innate antiviral immunity, a recent study reported that ROS production is beneficial for viral replication [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, timely relief of inflammation is essential for the regeneration of injured tissues. Many studies have shown that MOFs are promising anti-inflammatory materials [ 145–147 ]. For instance, Kang et al .…”
Section: Function Of Mofs In Mofs-based Biomaterials For Tissue Engin...mentioning
confidence: 99%
“…2 Optimization strategies for single-atom nanozymes at both framework structure and active center levels from MOFs have combined high catalytic properties for SOD and CAT, and can synergistically scavenge ROS (Fig. 3C) [22]. Another crystalline porous materials, COF, constructed through covalently linked organic units, show excellent properties for synthesizing SAzymes [23][24][25].…”
Section: Optimization Of Framework Structurementioning
confidence: 99%